Religious Moderation: The Harmonization of Religious Communities from the Perspective of Islamic Religious Education (A Case Study on FKAUB Malang) - Elsyam, Sulthan Fathani; Zainuddin, Muhammad; Jamilah, Jamilah (FONDATIA, 2025)
This research is driven by the growing issues of value disorientation and stagnation of tolerance in Indonesia, particularly in Malang—a region known for its religious diversity. These challenges significantly impact the progress of religious moderation, prompting an investigation into the strategies, implementation, and implications of the Interfaith Communication Forum (FKAUB) of Malang in promoting religious harmony. Employing a qualitative approach with purposive sampling, data were collected over a six-month period through observation, interviews, and documentation. The findings reveal that FKAUB Malang adopts a multifaceted strategy centered on education and socialization of religious moderation. This strategy is implemented through collaborations with interfaith training institutions and conflict mediation efforts grounded in local wisdom. Key programs include seminars, workshops, and interfaith youth forums, all aimed at fostering inclusive dialogue and mutual understanding among diverse religious communities. The practical contribution of this study lies in informing the development of inclusive Islamic Religious Education curricula and supporting the institutional strengthening of FKAUB initiatives. Theoretically, it enriches the discourse on religious education by illustrating the harmonizing role of interfaith forums in pluralistic societies. Despite its limitations as a single case study, the research offers valuable insights into localized strategies for building interfaith harmony and advancing religious moderation at the grassroots level.